SOFSEM 2012: theory and practice of computer science : 38th conference on current trends in theory and practice of computer science, spindlerův Mlyn, Czech Republic, January 21-27, 2012. Proceedings - Bielikova, Maria (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 38th Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2012, held in Špindlerův Mlýn, Czech Republic, in January 2012. The 43 revised papers presented in this volume were carefully reviewed and selected from 121 submissions. The book also contains 11 invited talks, 10 of which are in full-paper length. The contributions are organized in topical sections named: foundations of computer science; software and Web engineering; cryptography, security, and verification; and artificial intelligence.